Being a teacher becomes meaningful when interacting pedagogically. - Suárez de Lízcano, Olga (Rastros Rostros, 2023)
To exercise teaching within the professional range with student lovers of the construction of knowledge, implies to approach the pedagogical practice under the concept of pedagogy as the discipline especially susceptible to all specifically human process; with the purpose of giving account of the process that medullarly humanizes each student when assimilating and producing culture in each time and in each action of his life at individual and collective level.